Let's talk about sex[uality]‐related symptom burden in myeloproliferative neoplasms. Issue 12 (12th April 2016) - Gerds, Aaron T.
Abstract : A thoughtful conversation about sexual symptom burden should occur as part of a comprehensive assessment of the overall well‐being of patients with myeloproliferative neoplasms. In the article by Geyer et al in this issue of Cancer, the authors quantify the sexuality‐related symptoms, along with quality of life, in patients with myeloproliferative neoplasms, and evaluate how they correspond to disease features and treatment. See also pages 1888‐96.